Acculturation in the Inheritance Law of the Dayak Ngaju Community - Syaikhu, Syaikhu; Muzainah, Gusti; Adawiyah, Rabiatul (Universitas Islam Negeri Raden Intan Lampung, 2021)
The Dayak Community, as an agrarian community, respects and upholds the noble values of their ancestors. This value strongly affects their social and cultural system, including the customs and traditions of inheritance settlement. This research is descriptive-analytic using a phenomenology approach. The aim is to identify the uniqueness of the traditional heritage of the Ngaju Dayak tribe in Palangka Raya through the perspective of acculturation theory of culture and law. The study shows that the acculturation model that occurs in Palangka Raya is an adjustment model, in which the process of adjustment and adaptation of one culture to other cultures occurs without forming a new culture. In addition, this study also finds that the community kinship system influences the application of inheritance law among the Ngaju Dayak indigenous people, Palangka Raya, Central Kalimantan.